Penyapihan Dini Dengan Status Gizi Balita Usia 0-24 Bulan Di Posyandu Dusun Kedungbendo Desa Gemekan Sooko Mojokerto - Rizka Amelia (LPPM Sekolah Tinggi Ilmu Kesehatan Majapahit Mojokerto, 2013)
Early weaned doing with stopping give suck to children under five before 6 month. Children under five that early weaned inclined have less nutrient because giving mom’s milk relative few, so that is very influence to their growth and development. This researce have a purpose to know of relationship early weaned with nutrient status of children under five in Posyandu Kedungbendo Orchad Gemekan Village Sooko Subdistrict Mojokerto Regency. The desain of research use analytic correlation with cross sectional. The population of this research is all of mother with children under five of 0–24 month and wasn’t give suck that visite to the Posyandu Kedungbendo Orchad Gemekan Village Sooko Subdistrict Mojokerto Regency, have a lot of 52 respondent. And big sample is 46 respondent with simple random sampling technique. The variabel of research there are independent variable is early weaned and dependent variable is nutrient status of child under five age 0–24 month. The collection of data with questioner and observation of sheet, after tabulating then analise with Spearment test. That doing on June 12 2012. The result of research majority refer children under five early weaned have a lot of 27 children under five (58,7%) with less nutrient of status have a lot of 19 children under five (41,3%) and almost half children under five not early weaned have a lot of 19 children under five (41.3%) with more of nutrient status have a lot of 9 children under five (19,6%). That with Spearment test get the result p (0.000) < α (0.05). So H0 refused and H1 accepted, and can know that any relationship between early weaned with nutrient of status children under five 0–24 month. From this data can know that early weaned can influence nutrient of status children under five 0–24 month until need increase information about weaned, in order to mother know one five to weaning and give nutrient of food as side by mom’s milk.